2009
DOI: 10.1128/jcm.00605-09
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Genotypes of Helicobacter pylori in Gastric Biopsy Specimens from Patients with Gastroduodenal Pathologies in the Cukurova Region of Turkey

Abstract: The effects of Helicobacter pylori genotypes on clinical prognosis in the Cukurova region of Turkey were investigated by PCR. The prevalence of type I strains carrying the s1c allele, unlike in neighboring regions and countries, was found to be significantly higher in patients with gastritis and/or gastric ulcers (P ‫؍‬ 0.001), and that of type I strains carrying the s1a allele was found to be significantly higher in patients with duodenal ulcers (P < 0.001). The cagA gene was strongly associated with the more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
12
1
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 26 publications
6
12
1
5
Order By: Relevance
“…No s2m1 genotype was found in this study. This finding correlated confirm few data reported from other geographic regions of Turkey (6,10,18).…”
Section: H Pylori Genotypessupporting
confidence: 83%
See 3 more Smart Citations
“…No s2m1 genotype was found in this study. This finding correlated confirm few data reported from other geographic regions of Turkey (6,10,18).…”
Section: H Pylori Genotypessupporting
confidence: 83%
“…Our data similar to previous reports in Turkey where vacAs1a strains were showed to be significantly associated with PU (10,18), but different from a study in Turkey reported that vacAs1a strains were not found to be statistically associated with PU (26).…”
Section: H Pylori Genotypessupporting
confidence: 81%
See 2 more Smart Citations
“…For example, Yamaoka et al (1999Yamaoka et al ( , 2002 (Erzin et al, 2006;Nagiyev et al, 2009;Kolaylı et al, 2012;Ozbey et al, 2013;Yula et al, 2013). Similarly, our Cag A positivity rate (83.5 %) for H. pylori strains was in accordance with previous Turkish studies.…”
Section: Epiya-c and -D Have A Role In The Interaction Betweensupporting
confidence: 81%